Implementing Hudud is the responsibility of the ruler or his deputy (An Analytical Study) - Ali, Asst.Prof.Dr. Othman Ali Muhammad Al-Kriza (Sulaimani Journal for Humanities, 2025)
The research addresses the issue of implementing Hudood (prescribed punishments) in Islamic law, stating that they were legislated to preserve the objectives of Sharia. It notes that this serious responsibility is entrusted to the Sultan, ruler, or his deputy, according to the conditions and regulations stipulated by the Wise Legislator. The Imams have unanimously agreed that the implementation of Hudood, in all their forms, and discretionary punishments (ta'zirat) is the responsibility of the Imam, that is, the ruler or his deputy, and not of individuals. Therefore, no person, group, or organization may independently enforce Hudood. The wisdom behind this is to maintain security, prevent transgression, and protect against injustice. Otherwise, it would lead to chaos, disorder, the spread of lawlessness and corruption, and fear in society.